Juridical Analysis of the Process of Implementation of Crimination Related to Remedies for Clemency - Agus Sugiarto (Budapest International Research and Critics University, 2021)
The Unitary State of the Republic of Indonesia is a state of law. The 1945 Constitution stipulates that the Unitary State of the Republic of Indonesia is a legal state (rech stat), as evidenced by the provisions in the preamble, content, and explanation of the 1945 Constitution. This study aims to understand and analyze the president's authority to provide commutation of sentences based on positive law, as well as understand and analyze the purpose of granting leniency as a legal effort to oppose the implementation of the sentencing process. This research uses normative legal research, namely studying legal rules to determine legal principles, understanding vertical/horizontal synchronization, understanding all aspects of legal history, and understanding comparisons between legal systems. Based on the results of the research, the president has the right to accept and reject applications for leniency from death row, life imprisonment, and life imprisonment who have received fixed sentences from courts at all levels. The existence of leniency as a form of legal effort in the process of implementing decisions, both approval and rejection, must be based on the purpose of punishment, not administrative intervention, or presidential intervention in the judiciary, but the president grants clemency and leniency. Privileges have nothing to do with evaluating the judge's decision and cannot eliminate the perpetrator's crime.